Frequency of dermatophytosis in bovine (Bos indicus) of Córdoba department, Colombia - Cardona Alvarez, José (2018)
A retrospective study of bovine dermatophytosis was carried out through the clinical records between June 2007 and June 2017 of the Ambulatory Clinical Service of Large Animals of the Faculty of Veterinary Medicine of the University of Córdoba, Colombia. The aim was to determine the frequency of cutaneous dermatophytosis that occur in bovines (Bos indicus) in the Department of Córdoba. Of the 1184 dermatological cases attended in that period, 253 (21.4%) corresponded to cutaneous dermatophytosis in cattle. Of them, 54.6% were males. The most affected age group was the younger than 12 months with 56.2% (142/253). The location of the most common lesions was at the level of the body (chest and abdomen) (39.9%), neck (27.3%) and head (24.5%). There was no significant difference in the frequency of dermatophytosis with respect to age, sex and location of lesions.